Theoretical foundations of the development of social control in the system of state policy - Bokayev, B.N.; Yessengeldina, A.S.; Yessirkepova, A.M.; Kosherbayev, D.B.; Mussatayeva, A.A. (BUKETOV BUSINESS REVIEW, 2023)
Object: The article considers the features of the development of social control in the system of state policy. The authors of the article investigated various stages of the policy development and implementation process, offering opportunities for interaction between social control bodies and public authorities. Methods: With the help of general scientific research methods and comparative analysis, conclusions are drawn about the need to use social control for the process of planning and implementing policies, increasing the legitimacy, quality, understanding and long-term applicability of political initiatives. Findings: The article focuses on solving the issue of the subjectivity of social control institutions in the system of public policy: their identification, forms of cooperation, description of functions, principles of work, criteria of effectiveness and potential. Conclusions: Social control is carried out in order to implement State policy in accordance with the laws. The object of social control is all entities financed from the state budget. The logic of social control is based on the creation of intermediary institutions between the citizen and the state. To further improve the system of public policy, it is necessary to study the prospects for digitalization of social control institutions and the potential impact of this activity on the effectiveness of the functioning of the public administration system as a whole.